The prevalence of dietary related complementary and alternative therapies and their usefulness among cancer patients attending the Colney Cancer Center in the Norwich Area, United Kingdom - Van Tonder, Esmarie (Stellenbosch : Stellenbosch University, 2008)
Thesis (MNutr (Human Nutrition))--Stellenbosch University, 2008.